Resection rate of lung cancer in Teesside (UK) and Varese (Italy): a comparison after implementation of the National Cancer Plan. Issue 3 (26th November 2015) - Imperatori, Andrea; Harrison, Richard N; Dominioni, Lorenzo; Leitch, Neil; Nardecchia, Elisa; Jeebun, Vandana; Brown, Jacqueline; Altieri, Elena; Castiglioni, Massimo; Cattoni, Maria; Rotolo, Nicola
Abstract : Background: In a lung cancer survey in 2000 we showed significantly less favourable stage distribution and lower resection rate in Teesside (UK) than in the comparable industrialised area of Varese (Italy). Lung cancer services in Teesside were subsequently reorganised according to National Cancer Plan recommendations. Methods: For all new lung cancer cases diagnosed in Teesside (n=324) and Varese (n=260) during the 12 months October 2010 to September 2011 (hereafter 'the 2010 cohort'), demographic, clinico-pathological and disease management data were prospectively recorded using the same database and protocol as the 2000 survey. Findings were analysed focusing on resection rate. Results: In the 2010 cohort compared with 2000, both in Teesside and Varese emergency referral decreased (p<0.001), performance status improved (p<0.001), but cancer stage shift was not seen; resection rate improved in Teesside, from 7% to 11% (p=0.054), and was unchanged in Varese (24%). Moreover, in Teesside compared with Varese the stage distribution remained less favourable, stage I–II non-small cell lung cancer (NSCLC) proportion being respectively 12% and 19% (p=0.040), and resection rate in all lung cancers remained lower (11% and 24%; p<0.001). On multivariate analysis, resection predictors in Teesside were as follows: stage I–II NSCLC (OR 86.14; 95% CI 31.80 to 233.37), performance status 0–1 (OR 5.02; 95% CI 1.48 to 17.07), belonging to 2010 cohort (OR 2.85; 95% CI 1.06 to 7.64). Conclusions: In Teesside the main independent predictor of resection was disease stage; in 2010–2011 compared with 2000, lung cancer service improved but stage shift did not occur, and resection rate increased but remained significantly lower than in Varese.